Mechanisms of Intergenerational Environmental Stewardship Activated by COVID-19: Gratitude, Fairness, and Legacy Motives - Syropoulos, Stylianos; Markowitz, Ezra M. (Frontiers in Sustainable Cities, 2021)
The COVID-19 pandemic has caused an immense loss of human life, increased economic uncertainty, and negatively impacted individuals’ mental health and close relationships. At the same time, experts have noted a concurrent improvement in many environmental quality indicators, including significant decreases in both localized air pollution and global greenhouse gas emissions. These positive trends are due to changes in human behavior necessitated by social distancing and self-quarantining measures (e.g., reduced car and air travel). However, there is already evidence that these improvements in environmental quality are only temporary. This suggests that more intentional efforts will be necessary in order to maintain positive environmental benefits and address major environmental issues as the world gets back to some version of pre-pandemic economic and social activity. Still, our collective experience over the course of the pandemic provides clear evidence that such change is possible and on a rapid timetable. Our individual and collective responses to COVID-19 reveal that we do indeed have the ability to respond to novel societal threats in highly coordinated and effective ways, suggesting that confronting the existential threat of climate change may in fact be feasible. Here, we theorize that the COVID-19 pandemic has potentially activated and made more salient some key psychological mechanisms—including norms of fairness and reciprocity, feelings of gratitude, and consideration of personal legacies—that previous empirical work suggests can be harnessed to promote beneficent intergenerational decision-making aimed at solving the environmental challenges we and our descendants will face in the 21st century.